Moral Universalism: Measurement and Economic Relevance - Enke, Benjamin; Rodríguez-Padilla, Ricardo; Zimmermann, Florian (Management Science, 2022)
Many applied economic settings involve trade-offs between in-group members and strangers. To better understand decision making in these contexts, this paper measures and investigates the economic relevance of heterogeneity in moral universalism: the extent to which people exhibit the same level of altruism and trust toward strangers as toward in-group members. We first introduce a new experimentally validated, survey-based measure of moral universalism that is simple and easily scalable. We then deploy this tool in a large, representative sample of the U.S. population to study heterogeneity and economic relevance. We find that universalism is a relatively stable trait at the individual level. In exploratory analyses, heterogeneity in universalism is significantly related to observables: Older people, men, the rich, the rural, and the religious exhibit less universalist preferences and beliefs. Linking variation in universalism to self-reports of economic and social behaviors, we document the following correlations. Universalists donate less money locally, but more globally, and are less likely to exhibit home bias in equity and educational investments. In terms of social networks, universalists have fewer friends, spend less time with them, and feel more lonely. These results provide a blueprint for measuring moral universalism in applied settings and suggest that variation in universalism is relevant for understanding a myriad of economic behaviors. This paper was accepted by Yan Chen, behavioral economics and decision analysis.